ANALISIS FAKTOR PROMOSI, AKSESIBILITAS DAN BUKTI FISIK TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN (Studi pada Destinasi Wisata Gunung Beruk Desa Karangpatihan Kecamatan Balong Kabupaten Ponorogo) - Primadewi, Erika; Rispantyo, Rispantyo; Wardiningsih, Suprihatmi Sri (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
The marketing mix in tourism marketing includes 8P, which is an extension of the generally accepted traditional 4P. The eight "P" are product, price, place, promotion, packaging, programming, people and partnership. Some of these factors have a significant influence on the desire of tourists to visit the place or tourist destination concerned (Purnamasari, 2011: 15). This study aims to determine the effect of promotion, accessibility, and physical evidence the interest or decision of tourists visiting Mount Beruk Tourism Object Karangpatihan Village Balong District Ponorogo Regency. The data used in this study are primary data with data collection methods using questionnaire techniques. The sampling technique used was accidental sampling with data analysis performed using multiple linear regression analysis techniques. This research concludes that promotion influences tourist visiting decisions. Accessibility has no effect on tourist visiting decisions and physical evidence has an effect on tourist visiting decisions and all have a positive relationship with tourist visiting decisions. Based on the value of the coefficient of determination, when compared with a predetermined standard, it is in the current position.